2000
DOI: 10.1111/j.1540-8167.2000.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Dysfunction in Patients with So‐Called Lone Atrial Fibrillation

Abstract: Lone atrial fibrillation (AF) is defined by the absence of identifiable causes of AF, but its hemodynamics have not been investigated. Twenty-eight patients with lone AF were compared with 14 control patients referred for Wolff-Parkinson-White ablation. Transthoracic and transesophageal echocardiography were performed to rule out structural heart disease, followed by transseptally performed complete hemodynamic evaluation of the left heart systolic and diastolic function. There was no evidence of diastolic dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 18 publications
3
42
2
4
Order By: Relevance
“…Hence, it is affected directly by end-diastolic pressure and diastolic functions of the LV. The LA is also affected directly by compliance and pressure of the LV because it functions as a pump of the LV at the end of diastole [25][26][27]. In our study, the E/E m was decreased in the post-procedural period.…”
Section: Discussionsupporting
confidence: 49%
“…Hence, it is affected directly by end-diastolic pressure and diastolic functions of the LV. The LA is also affected directly by compliance and pressure of the LV because it functions as a pump of the LV at the end of diastole [25][26][27]. In our study, the E/E m was decreased in the post-procedural period.…”
Section: Discussionsupporting
confidence: 49%
“…In 2000, Jaïs, et al 24) found that the left ventricular end-diastolic pressure was higher in lone AF patients than in control subjects, suggesting the presence of left ventricular diastolic dysfunction in patients with lone AF. It has been demonstrated by Guazzi,et al 25) that the prognostic power of VE-VCO2 slope was superior to that of peak VO2 in patients with diastolic heart failure, in spite of a similar prognostic power of these indices in patients with systolic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The association between AF and diastolic dysfunction has been previously reported and diastolic dysfunction was a predictor of new onset AF [15,16]. The septal E/e' ratio, a diastolic parameter, is an easy and non-invasive echocardiographic marker of LV filling pressure.…”
Section: Discussionmentioning
confidence: 99%